Integration of Z-Source Converter in Active Harmonic Filtering - Ahfouda abdelkarim (University Eloued جامعة الوادي, 2024)
This thesis aims to design a three-phase shunt active power filter utilizing a Z-source inverter controlled by the instantaneous reactive power theory and a PI hysteresis control algorithm. The proposed structure is intended to mitigate harmonic components induced by nonlinear loads. Evaluation of the proposed structure's performance under various operating conditions with a nonlinear load was conducted. Simulation results using MATLAB/Simulink demonstrate satisfactory performance. Additionally, the proposed structure exhibited improved efficiency compared to conventional designs, highlighting its potential effectiveness. يتم التحكم فيه بواسط نظرية Z تهدف هذه الأطروحة إلى تصميم موشح طراق نشط ثلاثي الطور باستخدام عاكس مصدر يهدف الهيكل المقترح إلى تخفيف المكونات التوافقية الناتجة .PI الطاقة التفاعلية اللحظية وخوارزمية التحكم في التباطرؤ عن الأحمال غير الخطية. تم إجراء تقييم لأداء الهيكل المقترح في ظل ظوحف التشغيل المختلف مع الحمل غير الخطية أداءً مرضيًا. بالإضافة إلى ذلك، أظهر الهيكل المقترح كفاءة MATLAB/Simulink أظهرت نتائج المحاكاة باستخدام محسنة مقارنة بالتصاميم التقليدية ، مما يسلط الضوء على فعاليته المحتملة
Thèse doctorat
Keywords: filtre de puissance active shunt; théorie de la puissance réactive instantanée; Onduleur source Z; distorsion harmonique totale; تحويل موشح الطاق النشط; نظري القوة التفاعلي اللحظي; عاكس مصدر Z; التشوه التوافقي الكلي; shunt active power filter; instantaneous reactive power theory; Z-source inverter; total harmonic distortion